1979
DOI: 10.1097/00132586-197906000-00047
|View full text |Cite
|
Sign up to set email alerts
|

The Placental Transfer of Pancuronium and Its Pharmacokinetics during Caesarian Section

Abstract: The placental transfer of pancuronium and its pharmacokinetics were investigated in 33 pregnant women undergoing caesarean section. After a single intravenous injection of 60-100 pg/kg, the serum pancuronium concentration was measured (using a fluorimetric method) in serial samples of maternal blood and in umbilical arterial and venous blood obtained at the time of delivery. Detectable amounts of pancuronium were found in all foetal blood samples. The cord vein to maternal concentration ratio of pancuronium av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In 2 1 patients undergoing Caesarean section operation, Duvaldestin et al (1978c) showed a significant shortening of the elimination half-life of pancuronium (by 22 %), and a corresponding increase in total plasma clearance. However, since these changes are modest, they are not expected to produce resistance to the action of pancuronium.…”
Section: Caesarean Sectionmentioning
confidence: 96%
“…In 2 1 patients undergoing Caesarean section operation, Duvaldestin et al (1978c) showed a significant shortening of the elimination half-life of pancuronium (by 22 %), and a corresponding increase in total plasma clearance. However, since these changes are modest, they are not expected to produce resistance to the action of pancuronium.…”
Section: Caesarean Sectionmentioning
confidence: 96%
“…[64] In absence of suxamethonium chloride, the umbilical to maternal venous ratios for pancuronium bromide correlated with the dose-delivery intervaJ.l64. 236] In the presence of suxamethonium chloride, [236] there was no such correlation and the uptake of pancuronium bromide seems to be saturated. This should be a further indication that pancuronium bromide and suxamethonium chloride compete for the same mechanism of transport.…”
Section: 5 Fazadinium Bromidementioning
confidence: 99%
“…Support for this is provided by high Apgar scores and other clinical assessments, suggesting normal neonatal neurological and behavioural function. Dailey et al (1984) and Duvaldestin et al (1978b) also studied maternal pancuronium pharmacokinetics. In both studies the CL was significantly higher and t'hll shorter in women undergoing caesarean section than in patients having elective abdominal surgery (controls).…”
Section: Pregnancymentioning
confidence: 99%